„Starość? Sama definicja? To jest skomplikowane…”. Wokół rozumienia pojęcia starości przez przedstawicieli różnych pokoleń - Kramkowska, Emilia (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article discusses how the concept of old age is understood by representatives of the traditionalist generation, baby boomers, generation X and generation Y, who participated in qualitative research conducted in January–April 2022. The article is a comparative study of the presented viewpoints, and it attempts to explain their determinants as anchored in the profiles of each generation outlined in the literature. The analysis confirms that belonging to a particular generation determines the way in which old age is perceived. Recognising the diversity of definitions of old age exhibited by the respondents can be helpful in shaping attitudes of respect and tolerance, which are necessary for the consensual social coexistence of diverse generations.